Analysis of Hazard Analysis Critical Control Point in the Serabi Solo Shop - Ika Nawang Puspitawati; Laili Mabrur Rohma; Ahmad Thobroni Akbar; AR Yelvia Sunarti; Erwan Adi Saputro (Future Science, 2022)
Food is a basic human need. so that food hygiene needs to be considered so that it does not have a negative impact on human health. Many kinds of food are sold outside, such as regional food. To find out the critical point of food, it is necessary to study literature, observations and interviews with small industries. The purpose of this reaserch is to identify the preparation of HACCP (Hazard Analysis Critical Control Point) application on small industries, which is Serabi solo shop. From the observations made, a critical point hazard analysis will be carried out starting from the preparation of the Serabi solo material to packaging. The results show that the Serabi solo shop had 34.78% Prerequisite Programs. So the Serabi solo shop need more improvement to meet the standards of food safety management.